Анализ основных методов продвижения бизнеса в интернете - Верясова, А. Н.; Санин, А. А. (ХНУРЭ, 2014)
Today search for consumers has become a complex task for marketers. This is due to modern development of society and advertising. Advertising on the fences isn't working anymore and for good sales we have to comprehensively improve the distribution channels. Promotion of products on the internet has become a real panacea because of the relatively low cost of the advertising campaign on the Internet and high-quality effects resulting from Web marketing.
Keywords: метод продвижения бизнеса